SISTEM PAKAR UNTUK DIAGNOSA GANGGUAN PSIKOLOGIS ANAK DENGAN ALGORITMA BREADTH FIRST SEARCH (BFS): Array (JiTEKH, 2019)
Computers have now been used widely, especially in the Health sector. Today's computers / machines are equipped with various capabilities capable of recognizing human conditions, one of which is related to health. In this paper, the author will discuss the psychological health of children, including autism, ADHD and child disintegration. Early detection of psychological disorders in children using the BFS algorithm will produce an expert system that can help parents in early detection of their toddlers. Data on psychological disorders in the child will be coded according to the desired disturbance, then the results of the algorithm search will be displayed at the end of the application. The category of disorders that are entered based on the rules that have been made are 4 categories, namely normal, other disorders, autism, ADHD and child disitegation. The results obtained in this study state that the BFS algorithm can find psychological disorders in children in accordance with the rules that have been made based on child psychological experts.